A large-scale assessment of the healthcare burden of adhesive capsulitis of the shoulder joint - Samy Bouaicha; Karl Wieser; Philipp Kriechling; Stefan M. Scholz-Odermatt (Swiss Medical Weekly, 2020)
BACKGROUND AND AIM